SOME ORGANOPEROXO COMPLEXES OF ZIRCONIUM (IV), THORIUM (IV) AND URANIUM (VI) - Tarafder, M T H; Islam, M Shamsul; pal, s c; Khan, M R R (Biological Sciences - PJSIR, 2001)
Some new peroxo complexes of Zr (IV), Th (IV) and U (VI) containing organic ligands, L\ [N4Cl1IlC1I.oH)2); P, [N2CjHs(C6H.oH)J; LID,[(C6I-IjCNC2H4NH)2) and UV, [C6H4 NNH=CHC1I.oH] have been synthesized and char- acterized. These have compositions, [Zr(02)U], [Th(02) U] HP, [U(0)(02) LIT) H20, [U(0)(02) LIT],Zr (02)' LID], [Th(02)2 I}J) H20, [U(0)2(02) LID], [Zr(02)(SCN)Uv], Zr(02)(SCN)2 LID],and [Th(02)(SCN)Lrv 1The complexes are found to be inert towards oxidation of triphenylphosphine, triphenylarsine and allyl alcohol. The size of the metals as well as the electronic nature of the organic ligands influence the mode of coordination of the peroxo moiety. IR spectra reveal that VImode of Zr(02)' The (02) and U(02) groupings (i.e., 0-0 stretch) decreases with an increase in atomic number of metals in a particular group.